Pengaruh Kualitas Pelayanan Pajak, Tingkat Pendidikan, Pengetahuan Perpajakan, Sanksi Pajak dan Kesadaran Wajib Pajak terhadap Kepatuhan Wajib Pajak - Adelia Nitasari; Siti Nurlaela; Purnama Siddi (Owner : Riset dan Jurnal Akuntansi, 2023)
The research aims of it study was to determine how individual taxpayer compliance at KPP Pratama Karanganyar is impacted by a variety of tax service, education level, tax knowledge, tax sanction and taxpayer awareness. Thempopulationmin thismstudymwere 98.936 individualmtaxpayers registeredmat themKPP Pratama Karanganyar. It sampling technical used to proporsional random sampling, calculated using the Slovinmformula in order tomobtainma samplemsize of 100 respondents. Sourcewof data iswprimarywdatawthroughwquestionnaires. In addition, the data analysiswtechniquewusedwmultiple linearwregressionwanalysis. The resultswof this studywindicatewthat the of taxwknowledge, tax sanction and taxpayer awareness has ofwtaxation effectwindividualwtaxpayerwcompliance. Meanwhile, the quality of tax service and the level of education cannot effet on individual taxpayer compliance.